New approach for ontology matching using consensus theory - Văn Trung, Nguyễn; Bá Trí, Phan; Hữu Hạnh, Hoàng (Journal of Computer Science and Cybernetics, 2014)
The reuse of ontology has been an important factor in developing shared knowledge on the Semantic Web. However, this cannot completely reduce conflict potentials in knowledge bases. In the ontology integration process on the concept level, we need to determine the domain and range ofproperties of integrating ontologies. This paper presents an algorithm for ontology integration on concept level based on the consensus theory and an evaluation function of a similarity measure between concepts in its hierarchical structure. This paper also proves that the consensus theory is a useful tool for building collective knowledge from different sources.